2018
DOI: 10.3390/met8030180
|View full text |Cite
|
Sign up to set email alerts
|

Failure Analysis of PHILOS Plate Construct Used for Pantalar Arthrodesis Paper I—Analysis of the Plate

Abstract: Abstract:The failure of a proximal humerus internal locking system (PHILOS) used in a pantalar arthrodesis was investigated in this paper. PHILOS constructs are hybrids using locking and non-locking screws. Both the plate and the screws used in the fusion were obtained for analysis. However, only the plate failure analysis is reported in this paper. The implant had failed in several pieces. Optical and scanning electron microscopic analyses were performed to characterize the failure mode(s) and fracture surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 19 publications
3
15
0
Order By: Relevance
“…In general, the investigation showed that the failure was a result of conjoint bending/torsion loading and corrosion-fatigue cracking that propagated from the bottom of pit(s). The pitting susceptibility of this material is widely documented in the literature arising from inclusions, which were reported in Paper I [16]. The mechanisms governing failure of the screws are similar to that found for the plate [16].…”
Section: Fractographic Examinationsupporting
confidence: 53%
See 4 more Smart Citations
“…In general, the investigation showed that the failure was a result of conjoint bending/torsion loading and corrosion-fatigue cracking that propagated from the bottom of pit(s). The pitting susceptibility of this material is widely documented in the literature arising from inclusions, which were reported in Paper I [16]. The mechanisms governing failure of the screws are similar to that found for the plate [16].…”
Section: Fractographic Examinationsupporting
confidence: 53%
“…One of the locking screw heads and other undamaged locking screws remained in the plate after removal. In addition, one 6.5 mm cannulated screw fractured within five years of implantation, as was observed in the X-ray images [16]. No physical damage to the devices that may have led to the failure was observed.…”
Section: The Screwssupporting
confidence: 51%
See 3 more Smart Citations